Calibration of methylene‐referenced lipid‐dissolved xenon frequency for absolute MR temperature measurements. Issue 2 (14th September 2018) - Antonacci, Michael A.; Zhang, Le; Degan, Simone; Erdmann, Detlev; Branca, Rosa T.
Abstract : Purpose: Absolute MR temperature measurements are currently difficult because they require precalibration procedures specific for tissue types and conditions. Reference of the lipid‐dissolved 129 Xe resonance frequency to temperature‐insensitive methylene protons (rLDX) has been proposed to remove the effect of macro‐ and microscopic susceptibility gradients to obtain absolute temperature information. The scope of this work is to evaluate the rLDX chemical shift (CS) dependence on lipid composition to estimate the precision of absolute temperature measurements in lipids. Methods: Neat triglycerides, vegetable oils, and samples of freshly excised human and rodent adipose tissue (AT) are prepared under 129 Xe atmosphere and studied using high‐resolution NMR. The rLDX CS is measured as a function of temperature. 1 H spectra are also acquired and the consistency of methylene‐referenced water proton and rLDX CS values are compared in human AT. Results: Although rLDX CS shows a dependence on lipid composition, in human and rodent AT samples the rLDX shows consistent CS values with a similar temperature dependence (–0.2058 ± 0.0010) ppm/°C × T (°C) + (200.15 ± 0.03) ppm, enabling absolute temperature measurements with an accuracy of 0.3°C. Methylene‐referenced water CS values present variations of up to 4°C, even under well‐controlled conditions. Conclusions: The rLDX can be used to obtain accurate absolute temperature measurements in AT, opening new opportunities for hyperpolarized 129 Xe MR to measure tissue absolute temperature.